2022
DOI: 10.1109/jlt.2021.3134090
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Comparison of Modulation Schemes in Turbulent Underwater Optical Wireless Communications

Abstract: This paper presents an empirical comparison of different modulation schemes in still and turbulent water conditions. Using an underwater channel emulator, it is shown that pulse position modulation (PPM) and subcarrier intensity modulation (SIM) have an inherent resilience to turbulence induced fading with SIM achieving higher data rates under all conditions. Finally, the signal processing technique termed pairwise coding (PWC) is applied to SIM in underwater optical wireless communications for the first time.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The subcarrier intensity modulation (SIM) technique has been found to provide a resilience to the effects of turbulence induced fading by encoding data upon the phase, as well as the amplitude, of the transmitted subcarrier signal. 5 In our previous work on SIM, it was found that the highest data rates were achieved using SIM modulated with quadrature amplitude modulation (QAM). 5 The data rate of QAM-SIM could then be further optimised by applying the bit and power loading (BPL) technique, as in.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The subcarrier intensity modulation (SIM) technique has been found to provide a resilience to the effects of turbulence induced fading by encoding data upon the phase, as well as the amplitude, of the transmitted subcarrier signal. 5 In our previous work on SIM, it was found that the highest data rates were achieved using SIM modulated with quadrature amplitude modulation (QAM). 5 The data rate of QAM-SIM could then be further optimised by applying the bit and power loading (BPL) technique, as in.…”
Section: Introductionmentioning
confidence: 99%
“…5 In our previous work on SIM, it was found that the highest data rates were achieved using SIM modulated with quadrature amplitude modulation (QAM). 5 The data rate of QAM-SIM could then be further optimised by applying the bit and power loading (BPL) technique, as in. 6 Further to the properties of the carrier signal, the properties of light itself can be exploited as additional degrees of freedom for data transmission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the turbulence variation affected the SER performance remarkably. Geldard [15] combined PPM with subcarrier intensity modulation (SIM), and proposed pair‐wise coding (PWC) applied to SIM in UOWC for the first time, which demonstrated that PWC achieved a maximum data rate of 5.2 Gbps in still water condition.…”
Section: Introductionmentioning
confidence: 99%
“…VLC system is a potential candidate for many applications such as indoor positioning, underwater communications and internet of things (IoT). In addition, VLC system offers inherent security and can be employed in homes, offices and places where sensitive electronic devices exist such as in hospitals and areas where wired and radio-frequency (RF) wireless communications are not suitable [1], [2], [3]. Furthermore, it can enable significant energy and cost saving by reusing the existing lighting infrastructures for communication purposes [4].…”
Section: Introductionmentioning
confidence: 99%